2012
DOI: 10.5732/cjc.012.10035
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma metastatic to cervical lymph nodes from unknown primary origin: the impact of chemoradiotherapy

Abstract: The management of cervical lymph node metastases of squamous cell carcinoma from an unknown primary site is still a therapeutic challenge. We report here our experience in treating these patients with chemoradiotherapy as a curative approach. Data from 40 patients were reviewed. In total, 20 (50%) patients underwent excisional biopsy. All patients underwent radiotherapy, which was delivered to both sides of the neck and pharyngeal mucosa (extensive field), and concurrent chemotherapy consisting of weekly cispl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
2
10
0
5
Order By: Relevance
“…On multivariate analysis, lower N stage and ECE status was correlated with improved survival. The results are also consistent with those of previous reports (3)(4)(5)12,20,22). The current National Comprehensive Cancer Network (NCCN) guidelines for NUP (Version 1.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…On multivariate analysis, lower N stage and ECE status was correlated with improved survival. The results are also consistent with those of previous reports (3)(4)(5)12,20,22). The current National Comprehensive Cancer Network (NCCN) guidelines for NUP (Version 1.…”
Section: Discussionsupporting
confidence: 82%
“…Some case studies have revealed therapeutic outcomes of NUP treated by radiotherapy combined with surgery and/or chemotherapy, which are summarized in Table 5 (3,6,9,11,16,17,(19)(20)(21). Prognostic factors for survival are reported to be nodal stages, number of positive nodes, neck dissection, histopathological grading and ECE (3)(4)(5)7,9,19,20,22,23). In this series, the 5-year OS rate was 58.1%, similar to the data in the previous studies.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…En el grupo desfavorable, los pacientes usualmente reciben quimioterapia de forma empírica con intención paliativa, pero a pesar de esta tienen un mal pronóstico. Los subgrupos favorables son los más importantes y es a los que van dirigidos todos los esfuerzos, porque al identificarlos, recibirán un tratamiento específico, lo que mejora el pronóstico y algunos pueden tener supervivencia a largo plazo e incluso tener la posibilidad de curación (25)(26)(27)(28)(29)(30)(31)(32)(33). Entre ellos se encuentran los siguientes:…”
Section: Clasificaciónunclassified
“…Caveats include heterogeneity among studies with regard to tumor type, (neo)adjuvant treatment strategies, and study design. Other studies have suggested beneficial effects of CRT with regard to survival of cervical lymph node metastases from esophageal squamous cell carcinoma . In North American and European countries, different palliative treatment strategies are widely applied for patients with cervical lymph node metastases.…”
Section: Stage‐directed Individualized Therapymentioning
confidence: 99%